THE SOCIETAL IMPACT OF JAVA PLATFORM APPLICATIONS: A TECHNICAL ANALYSIS - Krishna Rao Vemula, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
This article examines the comprehensive impact of Java platform applications on modern society, exploring their influence across multiple sectors including enterprise systems, mobile technology, and digital transformation. The article investigates Java's core technological advantages in platform independence and scalability, analyzing its effects on business efficiency, social development, and environmental sustainability. The article demonstrates Java's significant contributions to economic growth through improved productivity, enhanced business processes, and creation of new digital markets. The article encompasses Java's role in revolutionizing healthcare delivery, educational access, and environmental monitoring while highlighting its future prospects in artificial intelligence, cloud computing, and sustainable development. The article reveals Java's fundamental role in shaping technological advancement and societal progress through its robust ecosystem and adaptable framework.